Antimicrobial activity of silver nano-particles synthesized from Bacillus tequilensis - Yasir Ayaz, Maria Shoukat, Shehla Shoukat, Anum Marwat, Robina, Bibi Zainab, Hazrat Abbas, Samra Sarwar, Shubana Hayat, Muhammad Zahid, Muhammad Ali (International Journal of Modern Agriculture, 2021)
Enteric diseases are considered as the most prevalent health related issues. Antibiotics are used to combat these diseases in a variety of ways. Numerous bacteria have developed resistance to these antibiotics, which is a major problem in health sector. Antibiotic resistance has prompted scientists to create new techniques. Bacillus tequilensis is a kind of bacterium that can help in synthesis of biological nanoparticles. The main objective of our study was to synthesize silver nanoparticles from Bacillus tequilensis and then to determine its antimicrobial activity. It was first proven by the color shift. Well diffusion method was used to test antibacterial activity. Muller Hinton agar medium was used to grow the strains. In contrast to Bacillus cereus, Escherichia coli showed a high vulnerability to these nanoparticles in antimicrobial assays. With regards to Escherichia coli, the maximum zone of inhibition was 15-25mm, whereas the lowest was 6-9mm against Bacillus cereus. Our study concludes that Bacillus tequilensis can be used to synthesize nanoparticles. It is possible to synthesize nan-oparticles on large industrial levels with a wide range of potential uses.